Education inequality and poverty: Evidence from sub-Saharan African countries / Folorunso Obayemi Temitope Obasuyi - Folorunso Obayemi , Temitope Obasuyi (2018)
Following the critical argument about education, human capital, growth and poverty, this study examined the levels of education inequality and further investigated how wealth was distributed across educational levels in twenty-five Sub-Saharan African (SSA) countries. It further determined the relationship between the education inequality and poverty, based on the SSA regional perspective and with the sampled twenty-five countries for comparative analysis. The study progressed to examine the proportion of dropout from schooling and the status of its spread. Methodologically, the thesis used cross-sectional data of Demographic Health Survey (DHS) where statistical procedures were followed. Furthermore, time series data on dropout were used to achieve the speed and the spread of the dropout. Using the educational attainment, the thesis measured the inequality of education with education inequality Gini, Lorenz Concentration Curve for wealth distribution and Generalised Lorenz Curve for gender decomposition. Due to the hierarchical characteristics of the data, structural equation modelling was used to estimate the coefficients of education inequality and poverty relationships for the 25 sampled countries. Furthermore, polynomial regression equation was used to determine the rate of dropout and used equilibrium point condition (EPC), the discriminant of the quadratic function to determine the status of the dropout spread. Firstly, the thesis findings on the levels of education inequality showed that 16 of the sampled countries representing 64% had education inequality (higher than 50%). Burkina Faso was at the extreme of over 90% of the inequality while Zimbabwe had 24% at the lower boundary of the distribution. About 32% of the sampled countries had their inequality skewed to female, including Cameroon, Cote D’Ivoire and Nigeria of the oil producing countries. Surprisingly, Comoros’ wealth was concentrated at lower boundary of education distribution while the remaining 24 countries were located at the upper boundary of the distribution - that is, higher levels of education. Nevertheless, the finding was still consistent with the existing assumption of educational promises. Secondly, findings showed that poverty significantly affected education inequality. Minding the oil producing countries, three of the six sampled countries had poverty impact above 50%. In general, Cameroon, Cote D’Ivoire and Mali had above 80% poverty impact. Thirdly, the dropout findings showed an inverted U-shaped curve, which displayed increasing and decreasing tides of dropout. However, the rate of dropout reduction fell below the rate of increase. Moreover, although large number of the countries had their dropout uncontrolled, but it was severely uncontrolled in Ethiopia. About gender, findings showed that only Ethiopia and Zambia have their rates of dropout higher for male than for female. Therefore, the thesis suggested, among others, that those oil producing countries affected with higher educational inequality should concentrate on equal distribution of oil rent proceeds. Likewise, because development depends on the human capital stock, before treating out-of-school problem, poverty that triggered educational inequalities should be addressed and speedily treated to accommodate development that people deserve. Finally, the pull and push strategies suggested in the thesis could be adopted to control the schooling dropout.